Entity Framework 4.0 Recipes A Problem-Solution Approach - Tenny, Larry. (Apress : Imprint: Apress, 2010)
Entity Framework 4.0 Recipes provides an exhaustive collection of ready-to-use code solutions for Entity Framework, Microsoft’s vision for the future of data access. Entity Framework is a model-centric data access platform with an ocean of new concepts and patterns for developers to learn. With this book, you will learn the core concepts of Entity Framework through a broad range of clear and concise solutions to everyday data access tasks. Armed with this experience, you will be ready to dive deep into Entity Framework, experiment with new approaches, and develop ways to solve even the most difficult data access challenges. If you are a developer who likes to learn by example, then this is the right book for you. Gives ready-to-use, real-world recipes to help you with everyday tasks Provides guideposts for learning core concepts Maps out key landmarks for experimenting with your own solutions.